2023
DOI: 10.1097/hc9.0000000000000131
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptome analysis revealed the immune profile of PD-1 blockade in gallbladder carcinoma liver metastasis

Abstract: Background: Gallbladder carcinoma is the most common cancer of the biliary tract, and the immune checkpoint blockade showed promising efficacy in the treatment of advanced gallbladder carcinoma. However, the underlying mechanisms remain unknown. Methods: Single-cell RNA sequencing was used to reveal immune cell dynamics in an anti-PD-1 responder with gallbladder carcinoma liver metastases. Gene set variation analysis, pseudotime analysis, single-cell regulatory network infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“… 51 As a marker of activated CD8+ T cells in ovarian cancer, 52 a high level of CXCL13 expression are found to be an indicator of “hot” TME, thus leading to a better prognosis in GBC patients receiving immunotherapy. 53 Tissue-resident CD103+CD8+ T cells exhibit persistent antitumor effects within tumor tissues and may serve as prognostic predictors. Patients with higher infiltration of these T cells tend to benefit more from ICI therapies.…”
Section: Immune Cells In Tumor Microenvironment (Tme) Of Btcmentioning
confidence: 99%
“… 51 As a marker of activated CD8+ T cells in ovarian cancer, 52 a high level of CXCL13 expression are found to be an indicator of “hot” TME, thus leading to a better prognosis in GBC patients receiving immunotherapy. 53 Tissue-resident CD103+CD8+ T cells exhibit persistent antitumor effects within tumor tissues and may serve as prognostic predictors. Patients with higher infiltration of these T cells tend to benefit more from ICI therapies.…”
Section: Immune Cells In Tumor Microenvironment (Tme) Of Btcmentioning
confidence: 99%
“…Use of the single-cell RNAseq technique allowed the demonstration of increasing heterogeneity and worse prognosis in more advanced hepatocellular carcinoma and showed that OPN expression correlated with tumor cell evolution and the reprogramming of the tumor microenvironment [ 145 ]. In gall bladder carcinoma, TAMs expressing OPN were associated with poor prognosis in PD-1-treated patients [ 146 ].…”
Section: Opn Mrna Expression In Tumor Cells and Tumor-associated Cellsmentioning
confidence: 99%